Echinacea purpurea supplementation does not enhance VO2max in distance runners - Baumann, C. W.; Bond, K. L.; Rupp, J. C.; Ingalls, C. P.; Doyle, J. A. (The Journal of Strength and Conditioning Research, 2014)
Oral supplementation of Echinacea purpurea (ECH) has been reported to increase levels of serum erythropoietin and as a result improve endurance performance in untrained subjects. The purpose of this study was to determine if ECH supplementation alters maximal oxygen uptake (VO2max) in trained endurance runners. Using a double-blind design, 16 trained endurance runners (9 ECH and 7 placebo [PLA]) supplemented with either 8,000 mg/d of ECH or wheat flour (PLA) for 6 weeks. Maximal aerobic treadmill tests and blood samples were measured before and after supplementation to determine VO2max, hematocrit (Hct), and hemoglobin (Hb). VO2max, Hct, and Hb did not differ between the ECH and PLA groups before or after supplementation. Furthermore, supplementation of ECH failed to improve VO2max (67.37 ± 4.62 vs. 67.23 ± 5.82 ml/kg/min), Hct (43.57 ± 2.38 vs. 42.85 ± 1.46%), or Hb (14.93 ± 1.27 vs. 15.55 ± 0.80 g/dL) from baseline measurements. Echinacea purpurea supplementation of 8,000 mg/d for 6 weeks failed to increase VO2max, Hct, or Hb in trained endurance runners and thus does not seem to influence physiological variables that affect distance running performance.